Hereditary Leukonychia Totalis: A Case Report and Review of the Literature - Kallapan Pakornphadungsit; Poonkiat Suchonwanit; Tueboon Sriphojanart; Pamela Chayavichitsilp (Karger Publishers, 2018)
Leukonychia is defined as white discoloration of the nails caused by an abnormal keratinization of the nail matrix. Congenital leukonychia totalis is a rare nail disorder, which is typically inherited in an autosomal dominant pattern. This condition can be presented as an isolated condition or in association with systemic diseases. We report a case of a 7-year-old Thai boy who developed asymptomatic white discoloration of all the nails since birth, with an absence of any predisposing factors or associated conditions.